Derangement of apoptosis in cancer - Eichhorst, Sören; Krammer, Peter H. (The lancet, 2001)
Cancer results when cells grow faster and live longer than normal. Therefore increased - activity of antiapoptotic proteins or decreased activity of proapoptotic proteins - can contribute to the development of cancer. Much progress has been made in the understanding - of how these changes occur. The importance of such knowledge is that inactivation - of apoptotic pathways may lead not only to the accumulation of cells but also to inability - of cells to respond to potentially harmful mutations, DNA damage, or chemotherapeutic - drugs.
Gesehen am 03.03.2021